2002
DOI: 10.1046/j.1464-410x.2002.03022.x
|View full text |Cite
|
Sign up to set email alerts
|

Priapism in sickle‐cell disease; incidence, risk factors and complications – an international multicentre study

Abstract: Objective  To define the incidence, risk factors and complications of priapism in a large population of patients with sickle‐cell anaemia in five centres in the UK and Nigeria, as priapism is common among these patients, but the precise characteristics of the condition in this population are poorly documented.Patients and methods  A questionnaire was developed and administered to patients with sickle‐cell disease. Questions were designed to define the incidence, nature, precipitants, duration, treatment and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
178
3
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(200 citation statements)
references
References 12 publications
10
178
3
9
Order By: Relevance
“…In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123]. Erectile dysfunction has been reported in as many as 21% to 35% and is likely a sequela of recurrent episodes of priapism [124,125]. Osegbe et al demonstrated that adult males with SCD, not taking hydroxyurea, have lower sperm count, motility and The participants assigned to hydroxyurea treatment had lower annual rates of crises than the participants given placebo (median, 2.5 vs. 4.5 crises per year, P < 0.001).…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123]. Erectile dysfunction has been reported in as many as 21% to 35% and is likely a sequela of recurrent episodes of priapism [124,125]. Osegbe et al demonstrated that adult males with SCD, not taking hydroxyurea, have lower sperm count, motility and The participants assigned to hydroxyurea treatment had lower annual rates of crises than the participants given placebo (median, 2.5 vs. 4.5 crises per year, P < 0.001).…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…Priapism, for example, is another complication resulting from sickle cell, as the corpora cavernosa of the penis are blood reservoirs prone to localized stasis, sickling, and obstruction of venous drainage [5,6]. The prevalence of this complication could be higher than previously described [7,8], as patients do not report short episodes or do not associate the symptoms with sickle disease [9][10][11], suggesting that better education of these patients is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…5 The lifetime probability for the development of clinically significant priapism is as high as 42% in men with SCD, and the rate of resultant ED exceeds 30%. 3,[6][7][8] Typically, there is a bimodal peak of incidence between 5 and 10 years in children and 20-50 years in adults. 9 By the time most men with SCD reach their twenties, greater than 75% of them will have already experienced their first episode of priapism, with the mean age of occurrence between 12 and 15 years old.…”
Section: Epidemiology Of Priapism and Patient Populations At Riskmentioning
confidence: 99%
“…9 By the time most men with SCD reach their twenties, greater than 75% of them will have already experienced their first episode of priapism, with the mean age of occurrence between 12 and 15 years old. 6,8,10,11 SCD is the most common etiology of priapism in childhood accounting for 63% of cases and is the primary etiology of ischemic priapism in 23% of adult cases. 12 The fact that SCD populations are affected to a greater degree by priapism emphasizes the public health significance of this problem and, more importantly, the need for education and preventive efforts in addressing solutions.…”
Section: Epidemiology Of Priapism and Patient Populations At Riskmentioning
confidence: 99%
See 1 more Smart Citation